Leveraging financing technology for sustainable fresh agricultural products financing in Indonesia - Karyani, Tuti; Perdana, Tomy; Sadeli, Agriani Hermita; Utami, Hesty Nurul; Renaldi, Eddy (Frontiers in Sustainable Food Systems, 2024)
Financial technology (fintech) offers farmers with athe prospect to of getting other finance sources apart from the established official funding institutions. Farmers of fresh Fresh Agricultural produce Products (FAP) in Indonesia have been receiving received financial offers from various fintech platforms. However, several platforms have failed to maintain their operations, resulting in a domino of negative consequences for the farming activities. This study's objective is to evaluate the viability of financial technology (fintech) as a fresh agricultural sector finance sourceexplore how fintech contributes to the sustainability of FAP by examining five key dimensions of sustainability, i.e., economic, social, environmental, technological, and institutional. The majority ofMost extant literature primarily examines the determinants that impact an individual's interest towards fintech lending. However, those existing research has notneeds to dedicated sufficient more attention to the sustainability of the platform and the enterprises it finances, with a particular emphasis on the fresh agriculturalFAP sector. A quantitative methodology was utilized to design the study, and a proportional stratified random sampling method was employed to select 269 fresh produceFAP producers as respondents. The data were analyzed using the Multidimensional Scaling (MDS) approach in Rap-Agrifin, using factors specifically designed to assess fintech sustainability in agribusiness. Fintech in the agriculture fresh productsFAP supply chain is classified as sustainable, according to the study's finding of multidimensions. Partially, the dimensions that acquire sufficiently sustainable value are the social dimensions, the economic dimensions, and the environmental dimensions, but less sustainable are the technological dimensions and the institutional dimensions are less sustainable. This research demonstrates that the MDS approach in Rap-Agrifin can effectively analyzed sustainable finance in agriculture, highlighting the need for focused improvement on institutional and technological factors, particularly through the application of fintech.